Atypical Brucella sp in captive Australian green tree frogs (Litoria caerulea): clinical features, pathology, culture and molecular characterization. Issue 5 (9th March 2020) - Latheef, S; Keyburn, A; Broz, I; Bagnara, A; Bayley, C; Frith, S; Dobson, EC
Abstract : Background: Brucella spp. are globally important zoonotic bacteria, which have historically been considered pathogens of warm‐blooded species. More recently, new strains of Brucella have been cultured from a broader range of animals including terrestrial and marine mammals and amphibians. These new isolates are classified as 'atypical' brucellae and differ from the classical stains by host tropism, phenotypic traits or phylogenetic distance. Atypical Brucella have previously been described as the cause of localised and systemic infection in frogs. Case report: This report describes the clinical features, pathology, microbiology and molecular characteristics of persistent Brucella spp. infection in two Australian green tree frogs and its isolation in an additional in‐contact, clinically well frog. Conclusion: The two frogs that died had severe nephritis attributed to brucellosis with disseminated infection identified in one animal.